Determination of Urinary Iodine Excretion to Assess Iodine Deficiency Disorder among Pregnant Women in District Hospital of Sindhupalchowk, Nepal - Singh, Vivek Kumar; Joshi, Anand Ballabh; Gurung, Chitra Kumar; Banjara, Megha Raj (Nepal Journal of Science and Technology, 2020)
Pregnant women and infants are risk populations of iodine deficiency disorders (IDD). Therefore, this study was designed to explore the status of IDD among pregnant women through the analysis of urinary iodine excretion (UIE). A total of 94 pregnant women from Chautara Hospital Sindhupalchowk were included to analyze UIE through Sandell-Kolthoff Reaction. Although the general clinical status of women was satisfactory, the urinary iodine excretion revealed that still, 18.0 percent of pregnant women in Sindhupalchowk had insufficient iodine intake. This indicates that pregnant women are still at risk of iodine deficiency disorder, and they should be in the priority population for the IDD prevention program.